Negotiating the disabled body : representations of disability in early Christian texts - Solevåg, Anna Rebecca (Early Christianity and its literature, 2018)
"Negotiating the Disabled Body explores how non-normative bodies are presented in early Christian literature through the lens of disability studies. In a number of case studies, Solevåg shows how early Christians struggled to come to terms with issues relating to body, health, and dis/ability. These efforts towards interpretation of unruly and extraordinary bodies appear in the texts in a multitude of ways, from healing in the Gospels to inflicting disability in the Acts of Peter) and from theologizing in Paul's letters to using disability as invective in Papias. Solevåg uses concepts of 'narrative prosthesis,' gaze and stare, stigma, monster theory, and crip theory to examine early Christian material to reveal the multiple, polyphonous, contradicting ways in which non-normative bodies appear"--